A Kernel Search Matheuristic to Solve The Discrete Leader-Follower Location Problem - Santos-Peñate, Dolores R.; Campos-Rodríguez, Clara M.; Moreno-Pérez, José A. (Networks and spatial economics, 2020)
In the leader-follower, ( r | p )-centroid or Stackelberg location problem, two players sequentially enter the market and compete to provide goods or services. This paper considers this competitive facility location problem in a discrete space. To solve it, the linear programming formulations for the leader and the follower are integrated into an algorithm which, in an iterative process, finds a solution by solving a sequence of these linear problems. We propose a matheuristic procedure that provides solutions for the leader via a kernel search algorithm. Taking into account binary and S-shaped customer choice rules, we present the computational results obtained and compare the exact algorithm with two versions of the kernel search procedure.